2019
DOI: 10.3892/mmr.2019.9976
|View full text |Cite
|
Sign up to set email alerts
|

Role of bone marrow mesenchymal stem cells in the development of PQ‑induced pulmonary fibrosis

Abstract: Paraquat (PQ) poisoning-induced pulmonary fibrosis is one of the primary causes of mortality in patients with PQ poisoning. The potential mechanism of PQ-induced pulmonary fibrosis was thought to be mediated by inflammation. Recently, bone marrow-derived mesenchymal stem cells (BMSCs) have been considered as a potential strategy for the treatment of fibrotic disease due to their anti-inflammatory and immunosuppressive effects. In the present study, an increased accumulation of BMSCs in a mouse model of PQ-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…In recent years, mesenchymal stem cells (MSCs) have received increasing attention in the field of regenerative applications, because of multi-lineage differentiation potential, migratory ability, and self-renewal properties [ 10 , 11 ]. MSCs are derived from a variety of organs and tissues, such as the bone marrow and adipose tissues, and can home to the sites of injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, mesenchymal stem cells (MSCs) have received increasing attention in the field of regenerative applications, because of multi-lineage differentiation potential, migratory ability, and self-renewal properties [ 10 , 11 ]. MSCs are derived from a variety of organs and tissues, such as the bone marrow and adipose tissues, and can home to the sites of injury.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested that MSCs have the capacity to suppress inflammation, reduce fibrosis, and prolong the survival time for preclinical models of PF, which was induced by bleomycin, silica, paraquat (PQ), and radiation [ 10 , 19 24 ]. However, the design projects, including MSC dose, type, route, source, and time interval, in each research are so different that the final therapeutic effect is difficult to evaluate.…”
Section: Introductionmentioning
confidence: 99%
“…The herbicide, PQ was reported to exhibit an elevated toxic impact on pulmonary tissues with the attributed mortality rate in human due to lung fibrosis [29] . Hydroxyproline content elevated significantly in the current study following PQ injection.…”
Section: Discussionmentioning
confidence: 99%
“…It was documented that the etiology for lung fibrosis was ascribed with inflammation and that various cytokine secretions were associated with induced pulmonary injury [29] . The present study revealed that the levels of CCL2, IL-6, TGF-β1, and IL-17 elevated significantly following PQ treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation